A Proactive Approach to Neonates Born at 23 Weeks of Gestation. Issue 5 (November 2015) - Backes, Carl H.; Rivera, Brian K.; Haque, Urbee; Srouji, Lara; Beck, Stacy; Yin, Han; Smith, Charles V.; Iams, Jay D.; Nelin, Leif D.
Abstract : OBJECTIVE: To evaluate in-hospital survival, survival without major morbidity, and neurodevelopmental impairment for neonates born at 23 weeks of gestation provided proactive, coordinated, and comprehensive perinatal and neonatal management. METHODS: This was a retrospective cohort study conducted at a single, tertiary care center between 2004 and 2013. Enrollment was limited to mother–neonate dyads at 23 weeks of gestation who were provided a proactive approach defined as documented evidence of antenatal corticosteroid administration, willingness to provide cesarean delivery for fetal distress, and neonatal resuscitation and intensive care. Among survivors, major morbidities (predischarge) and neurodevelopmental assessments at corrected ages of 18–22 months were examined. RESULTS: Among 152 live births identified, 101 neonates received proactive care, of whom 60 (59%) survived to hospital discharge. Preterm premature rupture of membranes (adjusted odds ratio [OR] 0.29, 95% confidence interval [CI] 0.09–0.94), fetal growth restriction (OR 0.16, 95% CI 0.03–0.89), delivery room cardiopulmonary resuscitation (OR 0.07, 95% CI 0.02–0.32), and prolonged intubation sequence (OR 0.15, 95% CI 0.05–0.45) were associated with lower neonatal survival. Among neonatal intensive care unit survivors, 62% had at least one major morbidity. Among 50 survivors with assessment at 18–22 months, six (12%) were unimpaired, 20 (40%) had mild impairment, and 24 (48%) had moderate or severe neurodevelopmental impairment. CONCLUSION: Proactive, interdisciplinary care enabled more than half of the neonates born at 23 weeks of gestation to survive, and approximately half of children evaluated at 18 months exhibited no or mild impairment. This information should be considered when providing prognostic advice to families with threatened preterm birth at 23 weeks of gestation. LEVEL OF EVIDENCE: II Abstract : Proactive, interdisciplinary care enables a majority of neonates born at 23 weeks of gestation to survive, and a majority of children evaluated at 18 months exhibit no or mild impairment.